Extraction and Purification of Lectin by Employing Anionic Surfactant Aerosol-OT Reversed Micellar System and Evaluation of its Antibacterial and Antioxidant Potentials - Rathnasamy, Senthilkumar; Deepika, S.S.; Vedha Hari, B.N. (Asian Journal of Chemistry, 2014)
Aloe vera is a high potential medicinal plant that contains many active biomolecules like proteins, sugars, amino acids and enzymes. In the present study, lectin from Aloe vera gel and Aloe vera leaf were extracted using non organic method. Sudden denaturation and incompatibleness in the conventional organic extraction method was overcome by biological extraction method. Lectin fractionation was done by ammonium sulphate precipitation and compared with reverse micellar extraction method. The protein content in the crude extracts was estimated to be 2.312 mg/mL and sample obtained after ammonium sulphate precipitation and reverse micellar extraction was found to be 1.77 and 2.068 mg/mL, respectively. The maximum activity fraction was collected and purified using cationic exchange chromatography on CM sepharose column. Purified fractions from the chromatographic column were collected and confirmed for the presence of lectin by native page analysis. The resulting fractions were assayed for haemagglutination activity using human erythrocytes, in vitro antibacterial activity using agar well diffusion method and in vitro antioxidant activity using reducing power assay. Results revealed that the extraction of lectin from Aloe vera leaf extracts using reverse micellar extraction is an effective method as compared to ammonium sulphate precipitation method and lectin was also found to possess high antioxidant activity with respective to the concentration of lectin and wide spectrum of antibacterial effect. A zone of inhibition against E. coli is (11 mm), of S. typhi (9 mm) is P. aeroginosa (9 mm), E. aerogenis (9 mm) and K. pneumonia (5 mm) were observed.